A cross-sectional study of the prevalence and severity of maxillofacial fractures resulting from motor vehicle accidents in Riyadh, Saudi Arabia - Ziyad AlHammad; Yanal Nusair; Sami Alotaibi; Razan Ababtain; Salma Alsulami; Ghada Aljumah (Saudi Dental Journal)
Objectives: To investigate the prevalence and severity of maxillofacial fractures resulting from motor vehicle accidents (MVAs) at King Abdulaziz Medical City (KAMC), Riyadh, Saudi Arabia. Materials and methods: A cross-sectional study of 325 males (89%) and 47 females (9%) was conducted that retrospectively reviewed records of patients referred to oral and maxillofacial surgery department from emergency department from 1st January 2016 to 31st December 2017 at KAMC, Riyadh. Results: A total of 372 subjects were included in the study. MVAs (80%) were the most prevalent cause of trauma. The age range most susceptible to MVAs was between 20 and 24 years old (28%). The most common site of fracture was the midface (64%), specifically orbit (32%). For mandibular fractures, the subcondylar was the most common site of fractures (19%). The most common treatment approach was conservative (65%). In terms of severity, approximately half of patients needed admission to the intensive care unit (ICU) (50%); the mean score on the Glasgow Coma Scale (GCS) was 11.34, but most scores fell in the mild range; and (68%) of subjects presented with other associated systemic injuries, especially orthopedic injuries (36%). Conclusions: MVAs were the main cause of trauma and affected mainly young males. The most common site of fracture was midface, specifically orbit. Subcondylar was the most prevalent fracture site for mandibular fractures. The severity of MVAs injuries was significantly higher compared to non-MVAs injuries. We suggest enforcing legislation and regulations on road safety such as the use of compulsory seat belts.